Diagraming the diagram determining the effectiveness of diagramming in an architectural design class - Joson, Gerard Thomas F. (2016)
A diagram is a visual spatialisation of ideas that help a designer navigate through a multitude of information. It can take any medium similar to sketches, illustrations and 3d models. To be an effective tool, the user needs to interact with the diagram, to produce new and exciting outputs.

This paper delves deeper into the often misunderstood but powerful diagramming tool used by architects worldwide. Discussions on diagrams are especially relevant in the academic discourse to expose design students with the mediating power of such tools in their design process. Students often struggle to successfully navigate through their ideas and concepts into unique architectural proposals leading to a worrying disconnect in their process. By creating the metrics for the effectiveness of diagrams as applied in the design process in an architectural design class, we, can mediate the gap between the input and output in students' designs.

Criteria formulated based on reading of current literature revealed the generative capacity of diagrams as placeholder for further exploration of unique architectural solutions. The criteria were tested with the author's Third Year Design class - Arch 31 in the UP College of Architecture. Progress was tracked through two design plates given in one semester and data was gathered through a survey and a focus group discussion. Evaluation of the output showed high effectiveness rating based on the created metrics and overall positive results revealing the great potential of integrating diagrams as a generative tool in a student's design process.
Keywords: Architecture -- Charts, diagrams, etc; Architectural drawing